"Long-term outcome in endometrial cancer patients after robot-assisted laparoscopic surgery with sentinel lymph node mapping". (April 2022) - Jebens Nordskar, Nina; Hagen, Bjørn; V Vesterfjell, Ellen; Salvesen, Øyvind; Aune, Guro
Highlights: The oncologic outcome after SLN algorithm is excellent and non-inferior to lymphadenectomy five years after surgery. None of the patients recurred later than 39 months after surgery. Patients treated according to the SLN algorithm had few long-term complications. Abstract: Objective: Sentinel Lymph Node (SLN) mapping is increasingly used as an alternative to lymphadenectomy in endometrial cancer. There is, however, limited data regarding the clinical outcome and survival after SLN mapping. The aim of the study was to determine long-term outcome data in endometrial cancer patients undergoing robot-assisted laparoscopic surgery and SLN mapping. Study design : Retrospective cohort study of 108 patients with primary endometrial cancer who underwent robot-assisted laparoscopic surgery and sentinel lymph node mapping using the Memorial Sloan Kettering Cancer Center (MSKCC) algorithm with near-infrared fluorescence detection of indocyanine green for endometrial cancer, from November 20th 2012 to January 1st 2016 at St. Olav's Hospital in Norway. The primary endpoint was recurrence-free survival. Secondary endpoints were overall survival and treatment complications. Results: Among 108 patients operated in accordance with the SLN algorithm, 17 (16%) had lymph node metastases. Adjuvant chemotherapy was administered on indication endometrial cancer to 36 (33%) of the patients. After a median follow up of 75 months (range 61–98), five (4.6%) patients had recurrence, and three patients had died from the disease. Four of the patients who had recurrence had lymph node metastasis at diagnosis. The 5-year recurrence-free survival was 95.4% (95% CI, 91.5 – 99.3). The 5-year disease-specific survival was 97.2% (95% CI, 94.1 – 100.3). The 5-year overall survival was 92.6% (95% CI, 87.7 – 97.5). Peripheral neuropathy after chemotherapy was the most common complication (9.3%), followed by lower limb lymphedema (2%) and postoperative hernia (2%). Conclusion: The present study demonstrated excellent oncologic outcome and low long-term treatment complication rate in patients treated according to the SLN algorithm more than five years after diagnosis.